Films on African music - Tracey, Andrew; Zantzinger, Gei (International Library of African Music, 1999)
"Mgodo wa Mkandeni"; "Mgodo wa Mbanguzi"; "The Chopi timbila dance"; "Mbira: the technique of the mbira dza vadzimu with Ephat Mujuru"; "Mbira: mbira dza vadzimu: religion at the family level with Gwanzura Gwenzi"; "Mbira: mbira dza vadzimu: urban and rural ceremonies with Hakurotwi Mude"; "Mbira: mbira dza vadzimu: Dambatsoko, an old cult centre with Muchatera and Ephat Mujuru"; "Mbira: Njari: Karanga songs in Christian ceremonies with Simon Mashoko"; "Mbira: Njari: Matepe dza mhondoro: a healing party"; "Ndando ya wusiwana"; "A spirit here today"; "Songs of the adventurers"; "Songs of the Badius"; "Dances of Southern Africa"
Keywords: African Music